2023
DOI: 10.34172/ehem.2023.09
|View full text |Cite
|
Sign up to set email alerts
|

Face mask use among pedestrians during the COVID-19 pandemic in Northeast Iran: A survey on 223,848 pedestrians

Abstract: Background: Despite the mass vaccination of people in countries, preventive health guidelines of coronavirus disease 2019 (COVID-19) are still one of the most critical factors for pandemic control. The objectives of this study were to assess the overall use of face masks and investigate the diverse kinds of face masks used among pedestrians in northeast Iran. Methods: This cross-sectional study was designed in Torbat Heydariyeh, northeastern Iran, from February 19 to May 13, 2020. A total of 223 848 pedestrian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The findings of our study showed that approximately half of the children wore masks regularly outside the home three months before the study. In Iran, a few studies have measured the use of masks in the general population, mostly involving adults [ 23 25 ]. The study by Rahimi, Shirali [ 23 ] found that 26.6 percent of pedestrians younger than nine and 45 percent of those between 10 and 39 years old wore masks.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of our study showed that approximately half of the children wore masks regularly outside the home three months before the study. In Iran, a few studies have measured the use of masks in the general population, mostly involving adults [ 23 25 ]. The study by Rahimi, Shirali [ 23 ] found that 26.6 percent of pedestrians younger than nine and 45 percent of those between 10 and 39 years old wore masks.…”
Section: Discussionmentioning
confidence: 99%